Colonial saints : discovering the holy in the Americas, 1500-1800 - Greer, Allan; Bilinkoff, Jodi, 1955- (Routledge, 2003)
"From the cult of Saint Anne to the devotees of the Virgin of Guadalupe, from Saint Anthony who competed with Christ for popularity in Brazil, to Jesuits who mixed freely with shamans that talked with the gods, this exciting new anthology examines the conversion of the colonized. The essays examine how New World spirits transformed into Old World saints - for example, the spirit of love transfigured into the Virgin Mary - as well as the implications of the canonization of the first American saint. Colonial Saints illustrates the complex and intimate connections among confessional life writing, canonization, and the practices of the Inquisition. There was a dynamic exchange involving local agendas, the courts in Spain and France, and, of course, Rome. This bold collection clearly shows the interplay between slavery and spirituality, conversion and control, and the links between the sacred and the political"--Publisher description